Optimizing additively manufactured macro-fin structure designs for enhanced pool boiling of dielectric fluids - Lum, Lucas Yu Xiang (2024)
This paper presents the results of the saturated pool boiling heat transfer performances of macrostructured fins fabricated by Selective Laser Melting, a metal additive manufacturing technique. A plain surface, two-dimensional triangular and rectangular fins, and three-dimensional pin and segregated fin array designs investigated in this study were fabricated using AlSi10Mg. A dielectric fluid, HFE-7100, was used as the cooling medium in a water-cooled thermosyphon to test the structures under atmospheric conditions. A macro-fin design optimization approach was developed by experimentally characterizing the boiling performances and bubble dynamics in fin arrays with different fin parameters such as fin topology, angle, and height. From the results obtained, this study optimized and tuned the macrostructure design to eliminate the detrimental bubble dynamics that were identified through high-speed visualization. Following a systematic study of the boiling characteristics of two-dimensional triangular and rectangular fins, and three-dimensional pin fins, the segregated fin array was developed to tackle the unfavorable bubble dynamics in these conventional fin geometries to enhance both critical heat flux and heat transfer coefficient. Various performance metrics were used to compare and evaluate the boiling performances of different fin topologies. From our studies, the segregated fin specimen (Seg-3) was determined to achieve the best balance between critical heat flux and heat transfer coefficient enhancements, attaining a critical heat flux of 64.19 W/cm2 and a maximum heat transfer coefficient of 2.22 W/cm2·K, enhancing critical heat flux and heat transfer coefficient by up to 97.2 % and 43.1 % as compared to the plain surface, respectively. Furthermore, Seg-3 has achieved boiling enhancements with only 334 mm2 and 50.6 mm3 of surface area and fin volume, respectively, a substantial surface area and fin volume reduction as compared to conventional macro-fin geometries with the same fin height. In all, this work not only provides fundamental insights into the bubble dynamics in various macro-fin structures and their influence on the boiling performance, but it also presents a macro-fin design optimization strategy that can be adopted for other immersion cooling applications.